Kajian Unsur Visual pada Ilustrasi Sampul Novel ‘Cogheart: Rahasia Detak Jantung’ - Ardian, Ardiyani; Patria, Asidigisianti Surya (Universitas Komputer Indonesia, 2022)
A novel needs several supporting aspects in order to compete well, such as an interesting storyline, clear character development, and a cover that is relevant to the storyline. A cover is not only protecting the pages of a book, but also the face of the story. Cogheart is a series of adventure fantasy-themed novels written by Peter Bunzl, a novelist and animator from London. This novel received high popularity and was awarded of the 2017 Sefton Super Reads Award and the 2018 Awesome Book Award. The purpose of this study is to describe the visual elements of the cover and analyze their relationship to the content of the story. The research method used is descriptive qualitative. This study uses the theory of design review to describe and explain each design element in the cover, which are: descriptive, formalistic, interpretation and evaluation. The results of the research show that each visual element in the novel represents the characters, setting of places, and crucial objects in the novel. The placement of these elements also symbolizes the unpredictable storyline.